Women on Corporate Boards and in Top Management - Fagan, Colette. author. aut Link
XIX, 288 p.
Keywords: This book examines the international trends and associated developments in gender equality policy including corporate governance such as gender quotas. International comparative analysis is combined with detailed analysis of eight European countries with different policy regimes and trajectories.